Sosialisasi Manajemen Asuhan Gizi Pasien melalui Penerapan Electronic Mecial Record (EMR) dengan QR Code dan Whatsapp di NCC - Rossalina Adi W; Riskha Dora Candra Dewi; Sustin Farlinda; Novita Nuraini (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The Nutrition Care Center (NCC) is a teaching factory (TEFA) at the Jember State Polytechnic (Polije) which provides assessment and diagnostic services for nutritional problems, comprehensive nutritional assessments, diagnostic services, nutritional counseling, and customized diet plans for clients. Health services, including nutrition, require accurate medical records that include patient identification, examination, treatment, interventions, and other relevant information. However, NCC faces challenges, namely that the medical recording system is still manual paper-based. Medical record numbers do not comply with numbering regulations, age is still used instead of date of birth, the nutritional assessment section is not yet standardized and disease code classification does not yet exist. This manual system is susceptible to damage, loss, and requires dedicated storage time and space. Since it was inaugurated in November 2021, the number of NCC visits has continued to increase both from internal clients and external clients of Polije with initiations with several educational institutions, offices and elderly groups. The use of EMR which is made easier with QR Codes and the application of Whatsapp Bot is the main alternative to build or improve the management of assessment and diagnostic services for nutritional problems according to client needs. Socialization of assistance in implementing Electronic Medical Records (EMR) with QR Code and WhatsApp Bot at NCC aims to make things easier for experts. nutrition to access the client's examination history, allergy history and previous therapy in one view and make it easier for clients to access medical record numbers without a card. This initiative is in line with the Department of Health Research Masterplan 2022 and the development of TEFA services. NCC recognized the need for a more efficient system and proposed implementing EMR with QR Codes and WhatsApp Bots to optimize patient care. This socialization was carried out at the Jember State Polytechnic NCC with the presence of participants from nutritionists, students, the community and administrators from NCC. This socialization obtained results in the form of increasing public understanding of nutritional care, especially in relation to the existence of NCC as a teaching factory at the Jember State Polytechnic, the use of EMR via QR codes and WhatsApp Bot as a solution implemented by NCC in optimizing patient care and increasing the empowerment of partners in using it. and implementation of EMR with QR codes and WhatsApp Bot in patient nutrition care at NCC.